Study of Fuzzy Logic Control of Dc-Dc Buck Converter - Duranay, Zeynep Bala; Guldemır, Hanifi (Fırat University, 2017)
Because of unspecified transfer function of dc-dc converters fuzzy controllers can be used instead of classical controllers. The design of fuzzy controllers does not require an exact mathematical model. Instead they are designed based on general knowledge of the plant. In this paper, a fuzzy logic controller for a dc-dc buck converter is designed. The designed controlled system is simulated in MATLAB/Simulink software.  Different parameters such as input voltage and output load are varied and the responses of fuzzy controller to these variations have been studied and investigated in order to evaluate the designed controller performance. The simulation results are presented. Fast dynamic response of the output voltage and robustness to load and input voltage variations are obtained.